1970
DOI: 10.1042/cs0390769
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of pH, Bicarbonate and Hypertonicity on the Absorption of Ammonia from the Rat Intestine

Abstract: 1. Ammonia absorption has been studied in closed loops of rat jejunum, ileum and colon.2. Ammonia absorption was significantly greater from solutions buffered at higher pH. Absorption was also greater in the presence of the bicarbonate ion, and this effect was not due solely to the influence of bicarbonate upon the initial pH of the solutions studied. In the presence of ammonia net bicarbonate absorption was increased and net bicarbonate secretion was decreased.3. The above effects are compatible with the hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

1972
1972
2000
2000

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…The major source appears to be bacterial hydrolysis of endogenous urea, which contributes about 150 mmol of ammonia a day (Walser & Bodenlos, 1959;Richards, Metcalfe-Gibson, Ward, Wrong & Houghton, 1967) if all the urea degraded in the body has this fate, as appears to be the case (McDermott et al, 1954;Jones et al, 1969). However, observations by Wolpert, Phillips & Summerskill (1971) suggest that most of this urea never reaches the colonic lumen, being hydrolysed by bacterial ureases within the colonic mucosa and absorbed directly into the blood stream.…”
Section: Discussionmentioning
confidence: 90%
“…The major source appears to be bacterial hydrolysis of endogenous urea, which contributes about 150 mmol of ammonia a day (Walser & Bodenlos, 1959;Richards, Metcalfe-Gibson, Ward, Wrong & Houghton, 1967) if all the urea degraded in the body has this fate, as appears to be the case (McDermott et al, 1954;Jones et al, 1969). However, observations by Wolpert, Phillips & Summerskill (1971) suggest that most of this urea never reaches the colonic lumen, being hydrolysed by bacterial ureases within the colonic mucosa and absorbed directly into the blood stream.…”
Section: Discussionmentioning
confidence: 90%
“…In mammalian organs this process has been found to account for diffusion equilibrium of ammonia across the renal tubular epithelium (Orloff & Berliner, 1956;Coe & Korty, 1967) and ammonia absorption through the mucosae of stomach (Fleshler & Gabuzda, 1965), ileum (Swales et al, 1973), colon (Swales et al, 1970;Price, Sawada & Voorhees, 1970;Castell & Moore, 1971;Down, Agostini, Murison & Wrong, 1972) and urinary bladder (Rosenfeld, Aboulafia & Schwartz, 1963).…”
Section: Discussionmentioning
confidence: 97%
“…Hydrazine is a non-physiological compound with a close structural similarity to ammonia and similar physical properties except that it is not volatile at normal temperatures ( Table 1). It exhibits pH-dependent movement through many biological membranes (Orloff & Berliner, 1956 Wrong, 1970;Swales, Papadimitriou & Wrong, 1973), a finding which suggests diffusion in the un-ionized form. In our present studies absorption across the oral mucosa was pH-dependent ( Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Some 30 min after mounting the tissue in the chambers, 22 Na (59 kBq) and 36 Cl (29 kBq) were added to one side of the epithelium (labelled side). When blockers were present, they were added immediately before the radioisotopes to the mucosal solution.…”
Section: Measurement Of Unidirectional Ion Fluxesmentioning
confidence: 99%
“…Earlier studies have suggested that absorption is due mainly to non-ionic diffusion of unprotonated NH 3 . This thought was based on the observation that the absorption of ammonia correlates positively to the absorption of bicarbonate [8,36]. From the latter observation a concept was developed in which secreted bicarbonate titrates NH 4 + to NH 3 , thereby forming CO 2 which is reabsorbed together with NH 3 , the latter by non-ionic diffusion.…”
Section: Introductionmentioning
confidence: 99%